SdiA, a Quorum-Sensing Regulator, Suppresses Fimbriae Expression, Biofilm Formation, and Quorum-Sensing Signaling Molecules Production in Klebsiella pneumoniae - Pacheco, Thaisy; Gomes, Ana Érika Inácio; Siqueira, Nathália Maria Gonçalves; Assoni, Lucas; Darrieux, Michelle; Venter, Henrietta; Ferraz, Lúcio Fábio Caldas (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae is a Gram-negative pathogen that has become a worldwide concern due to the emergence of multidrug-resistant isolates responsible for various invasive infectious diseases. Biofilm formation constitutes a major virulence factor for K. pneumoniae and relies on the expression of fimbrial adhesins and aggregation of bacterial cells on biotic or abiotic surfaces in a coordinated manner. During biofilm aggregation, bacterial cells communicate with each other through inter- or intra-species interactions mediated by signaling molecules, called autoinducers, in a mechanism known as quorum sensing (QS). In most Gram-negative bacteria, intra-species communication typically involves acyl homoserine lactone (AHL) autoinducers and two proteins: LuxI synthase produces the signal molecules and LuxR transcription factor is their cognate receptor. However, K. pneumoniae does not produce AHL but encodes SdiA, an orphan LuxR-type receptor that responds to exogenous AHL molecules produced by other species. While SdiA regulates the expression of virulence factors in many pathogens, the role of this regulator in K. pneumoniae pathogenicity remains unknown. In this study, we describe the characterization of sdiA mutant strain of K. pneumoniae. The sdiA mutant strain has increased biofilm formation, which correlates to the increased expression of type 1 fimbriae, thus revealing a repressive role of SdiA in fimbriae expression and bacterial cell adherence and aggregation. On the other hand, SdiA acts as a transcriptional activator of cell division machinery assembling in the septum, since cells lacking SdiA regulator exhibited a filamentary shape rather than the typical rod shape. We also show that K. pneumoniae cells without SdiA regulator present constant production of AI-2 molecules at maximum levels, suggesting a putative role for SdiA in the regulation of the production of AI-2. Taken together, our results demonstrate for the first time that K. pneumoniae SdiA acts in the pathogenesis of K. pneumoniae by controlling cell division, fimbriae expression, biofilm formation, and production of QS autoinducers.